ANALISIS PENGARUH PERILAKU KONSUMEN, DAYA TARIK IKLAN DAN PERSEPSI KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN AIR MINUM DALAM KEMASAN MEREK VIZ (Studi Kasus Pada PT. Citra Golden Tunggal, Kota Pangkalpinang) - Yuliana, Ika; Ruben Manullang, Rizal; Medinal (Jurnal Progresif Manajemen Bisnis, 2018)
The study aims to prove the influence of Consumer Behavior, Ads Attraction, and Perception of Product Quality towards Purchasing Decision. The analysis was using Multiple Linier Regression after doing some test such as Validity Test, Reliability Test and Classical Assumption Test, including a Multicolliearity and Normality. The result of this study shows if Consumer Behavior, Ads Attraction and Perception of Product Quality have a positive impact towards Purchasing Decision. Partially speaking, the result of t-count shows that Consumer Behavior has a significant effect towards Purchasing Decision (3,981>2,00172). The Ads Attraction has a significant effect towards Purchasing Decision (3,601>2,00172) and The Perceptions of Product Quality also partially has impacts towards Purchasing Decisions by t-count 3,852 that is greater than t-table2,00172. Simultaneously, Consumer Behaviour, Ads Attraction and Perception of Product Quality were able to predict nor explains the Purchasing Decision with determine by a Coefficient of Determination (R2) of 0.682. In other word, 68,2% those variable can be use as factors which can explains the Purchasing Decision.